Relationship Between Leadership Style, Work Engagement, Performance Management System and Impact for Productivity Employee - Adhiya Mizvi; Dana Farhana; Luk Luk Fuadah (Dinasti International Journal of Education Management and Social Science, 2025)
This study presents a systematic literature review that explores the complex relationships between leadership style, work engagement, performance management systems (PMS), and employee productivity. Guided by the PRISMA protocol, a total of 57 peer-reviewed articles published between 2020 and 2025 in Scopus-indexed journals (Q1–Q4) and SINTA-indexed journals (Level 2–4) were analyzed. The findings indicate that transformational leadership consistently exerts the strongest positive influence on work engagement and employee productivity, whereas laissez-faire leadership demonstrates negative effects. Work engagement emerges as a key mediating variable that translates leadership influence into productive work behaviors. PMS functions as an organizational infrastructure that moderates and, in some cases, mediates the leadership–performance relationship, with adaptive and fair systems producing superior outcomes. The integration of leadership, work engagement, and PMS generates a synergistic effect that contributes to sustained and measurable productivity improvements. This review contributes to the literature by offering a comprehensive integrative framework for understanding the interconnected role of leadership, engagement, and PMS, while also providing theoretical insights and practical implications for enhancing organizational effectiveness.